PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA KOMIK UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN SISWA PADA TEKS CERITA KELAS 4 SD KUSUMA PUTRA - Rizky Ramadhany, Tisna; Binti Mirnawati, Lilik; Dian Ayu Afiani, Kunti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to measure the improvement in students' reading comprehension skills using a problem based learning approach in Indonesian. The Classroom Action Research (PTK) method was applied, focusing on grade IV students at SD Kusuma Putra Surabaya, a total of 32 students. This approach was explored for its impact on reading comprehension skills. Data collection is carried out through observation, tests and documentation with various instruments such as observation sheets, teaching modules and test grids. Data analysis involves quantitative and qualitative techniques. The results show an increase in reading comprehension skills from the first to the second cycle. In the first cycle, 65.62% of students met the Minimum Completeness Criteria (KKM), while 34.37% of students did not. The second cycle showed an increase, with 81.25% of students meeting the KKM and 18,75% not yet. The use of comics as a learning medium in Indonesian language learning has proven effective in improving students' reading and comprehension skills.